Theory and practice of digital libraries - Zaphiris, Panayiotis; Rasmussen, Edie; Loizides, Fernando (My University, 2012)
This book constitutes the refereed proceedings of the Second International Conference on Theory and Practice of Digital Libraries, TPDL 2012 - the successor of the ECDL (European Conference on Research and Advanced Technology for Digital Libraries) - held in Paphos, Cyprus, in September 2012. The 23 full papers, 19 short papers, 15 posters and 8 demonstrations presented in this volume were carefully reviewed and selected from 139 submissions. The papers are organized in topical sections on user behavior, mobiles and place, heritage and sustainability, preservation, linked data, analysing and enriching documents, content and metadata quality, folksonomy and ontology, information retrieval, organising collections, as well as extracting and indexing.
Keywords: Human-computer interaction; Search engine; User-centered system design